The Influence of the Make A Match Cooperative Learning Model on the Learning Outcomes of Class V Students at Animal Life Cycle Material at Cimuncang State Elementary School - Sri Wahyuni (CV. Rayyan Dwi Bharata, 2023)
Science learning is one of the material loads that often appears in learning because it is directly related to the student's environment. In the implementation of science learning, the teacher plays an important role in creating interactive learning conditions so that learning objectives can be conveyed. This study aims to determine the effect of the make a match cooperative learning model on the learning outcomes of fifth grade students on animal life cycle material at Cimuncang Elementary School. The research method used in this study was an experimental non-equivalent control group design. This research was conducted at SDN Cimuncang. The population used in this study were all fifth grade students at SDN Cimuncang, totaling 30 students. The sample used is the entire population (total sampling), for sampling using simple random sampling. For data collection techniques using tests, namely pretest and posttest and data were analyzed using the SPSS 24 application. From the results of the data that had been analyzed, sig. (2-tailed) 0.002 and 0.003 0.05 which means H0 is rejected. Obtain data normality 0.017 0.05, and the significance level of data homogeneity is 0.47 0.05. The average value of the experimental class was 85.13 and that of the control class was 77.13 (85.13 77.13). So the Cooperative Learning Type Make A Match learning model has a positive influence on student learning outcomes in Animal Life Cycle material in class students V SDN Cimuncang.